2000
DOI: 10.3109/07853890008995947
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of adolescent drug use on psychiatric disorders in early adulthood

Abstract: This article summarizes the existing literature on the relationship between adolescent drug use and abuse and the development of psychiatric disorders in adulthood. In recent years, there has been increased awareness of the co-occurrence of drug abuse and psychiatric disorders in adolescence and young adulthood. Few longitudinal studies, however, have examined specifically the impact of earlier drug use and abuse on later psychiatric disorders. The literature suggests three possible models to explain the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 60 publications
1
29
1
Order By: Relevance
“…Parents should be aware of potential non-prescribed use of commonly prescribed pain relievers by their children and monitor their frequency and dosing of medical use as needed. Epidemiological evidence indicates that adolescents manifesting early drug use are likely to need clinical attention, especially in the presence of other risk factors, such as psychiatric problems, genetic predisposition, or adverse environments (Anthony and Petronis, 1995;Brook et al, 2000;Costello, 2007;Tsuang et al, 1998). To what extent early use of non-prescribed pain relievers is related to subsequent drug use and factors modifying the risk for adverse outcomes deserves investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Parents should be aware of potential non-prescribed use of commonly prescribed pain relievers by their children and monitor their frequency and dosing of medical use as needed. Epidemiological evidence indicates that adolescents manifesting early drug use are likely to need clinical attention, especially in the presence of other risk factors, such as psychiatric problems, genetic predisposition, or adverse environments (Anthony and Petronis, 1995;Brook et al, 2000;Costello, 2007;Tsuang et al, 1998). To what extent early use of non-prescribed pain relievers is related to subsequent drug use and factors modifying the risk for adverse outcomes deserves investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in this review demonstrated that adolescents engaging in NMUPM often have underlying mental health problems [8,10,16,18]. Access to treatment for underlying psychological issues that place adolescents at increased risk for NMUPM must also be improved, particularly for those who have other risk factors, such as troubled environments, traumatic histories, delinquent behavior, or polysubstance use [18,[45][46][47][48]. Thus, the complexity of treating and preventing adolescent NMUPM requires effort from multiple stakeholders at various levels.…”
Section: Implications For Treatment and Preventionmentioning
confidence: 99%
“…Previous research has documented that internalizing symptoms in childhood predict depression during adolescence (Rose, Rose, and Feldman, 1989). Externalizing behaviors (i.e., aggression, delinquency) predict later problem behaviors including drug use and antisocial behavior (Brook, Whiteman, Finch, and Cohen, 1996), as well as psychiatric disorders (Brook, Richter, and Rubenstone, 2000). Therefore, it is important to identify the predictors of internalizing symptoms and externalizing behaviors among children.…”
mentioning
confidence: 99%